Strategic industrial policy in the European Union: The uneven geography of Important Projects of Common European Interest (IPCEIs) participation - Manica, L.; Damásio, B.; Mendonça, S. (New Political Economy)
This article examines whether Important Projects of Common European Interest (IPCEIs) mitigate or intensify inequalities in the geography of state aid across European Union (EU) Member States. It provides the first systematic empirical assessment of IPCEI distribution across all initiatives approved up to 2025. Integrating core-periphery dynamics with state capacity, strategic coupling in European value chains and path dependence, it argues that IPCEIs create upgrading opportunities only where sectoral alignment and administrative capabilities jointly meet demanding project requirements. The analysis shows that absolute IPCEI support is heavily concentrated in core economies, while several peripheral and semi-peripheral countries display disproportionate commitment intensity relative to their overall state aid. Participation does not map onto a simple core-periphery rift; instead, a multi-tier structure is emerging as a subset of lower-capacity states remains consistently excluded. Overall, IPCEIs operate as selective levelling mechanisms: they can enable peripheral upgrading under specific conditions while simultaneously reinforcing stratification in EU industrial policy governance, such that core dominance is not incidental but structurally embedded in how the instrument operates.